Waarom verlaat verpleegkundiges die beroep? - A.M. Venter (AOSIS, 1983)
An investigation was done to determine the factors which influence registered nurses to leave the nursing profession. Two critical factors were found to be salaries and unpopular working hours. Other factors appeared to be less significant. The author makes a number of recommendations, including suggestions about salaries, hours of duty, recruitment and the status and image of the nursing profession.